1973
DOI: 10.1351/pac197335030283
|View full text |Cite
|
Sign up to set email alerts
|

The control of aflatoxin residues in food of animal origin

Abstract: Apart from its pr.esence in primary agricultural products, aflatoxin and its metabolites may be detected in animal tissues and milk. As the aflatoxins are toxic and extremely carcinogenic, control of food contamination with them is imperative. Either the primary aflatoxins (B 1 , B 2 , G 1 andG 2 ) or their metabolites (M 1 and M 2 ) have been recovercd from several animal tissues and milk. The bio-assay techniques which are currently available arenot suitable for routine screening purposes. The chemical assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1975
1975
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Contradictory data have been reported on the influence of milk concentration on AFM 1 . Kiermeier (1973) reported no losses of AFM 1 , whereas some authors observed losses ranging from 60 to 75% following milk concentration (Moreau, 1976;Purchase, I. F. H., 1973). Data from the studies on the occurrence of AFM 1 in milk since the 1990s are reported in ( Many authors showed that Seasonal effect influences concentration of aflatoxin M 1 .…”
Section: Regionmentioning
confidence: 99%
“…Contradictory data have been reported on the influence of milk concentration on AFM 1 . Kiermeier (1973) reported no losses of AFM 1 , whereas some authors observed losses ranging from 60 to 75% following milk concentration (Moreau, 1976;Purchase, I. F. H., 1973). Data from the studies on the occurrence of AFM 1 in milk since the 1990s are reported in ( Many authors showed that Seasonal effect influences concentration of aflatoxin M 1 .…”
Section: Regionmentioning
confidence: 99%